Upaya Meningkatkan Hasil Belajar Lay-Up Shoot Dalam Permainan Bola Basket - Amrizal Amrizal; Seri Mughni Sulubara (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
Basketball is a two-squad game played by 5 players in one team. Many factors can support good basic basketball skills, including the lay up shoot movement. This study aims to determine the learning outcomes of lay up shoot in basketball games. This study uses a class action research approach. The population in this study were all second semester aceh mahakarya university PE students. The sample of this study the author set a total sampling sample of 20 people. Research techniques in two cycles of learning. The method used in this research is descriptive method, which is a method or technique that reveals clear facts about the symptoms that exist in a research object, the data collection tool used is an observation sheet. After conducting the research, it was concluded that the results of basketball game skills were not good only 4 students (20%) after doing cycle I and Cycle II on lay up shoot techniques in basketball games the skill results were very good with as many as 16 students (96%) on basketball playing skills.